Conditional inactivation of the BRCA1 tumour suppressor gene in the mouse ovarian surface epithelium in vitro and in vivo - Clark-Knowles, Katherine Victoria (University of Ottawa (Canada), 2007)
Epithelial ovarian cancer (EOC) is thought to arise from the ovarian surface epithelium (OSE); however the molecular events underlying this transformation are poorly understood. Germline mutations in the BRCA1 tumor suppressor gene result in a significantly increased risk of developing EOC and a large proportion of sporadic EOCs display some sort of BRCA1 dysfunction. Using mice with conditional expression of Brca1, we inactivated Brca1 in the murine OSE and demonstrate that this inactivation results in the development of preneoplastic changes, such as hyperplasia, epithelial invaginations, and inclusion cysts, which arise earlier and are more numerous than in control ovaries. These changes resemble the premalignant lesions that have been reported in human prophylactic oophorectomy specimens from women with BRCA1 germline mutation. While tumourigenesis was not observed when Brca1 was inactivated on its own, it was found that inactivation of Brca1 accelerated tumour progression in animals in which the p53 tumour suppressor had also been inactivated in the OSE, an effect that was not observed with concomitant inactivation of the Rb tumour suppressor gene. Inactivation of Brca1 in primary cultures of murine OSE cells led to a suppression of proliferation due to increased apoptosis that could be rescued by concomitant inactivation of p53 and/or Rb, however only concomitant inactivation of p53 led to the ability of Brca1-deficient MOSE cells to grow in an anchorage-independent manner. Brca1-deficient MOSE cells displayed an increased sensitivity to the DNA damaging agent cisplatin and were modestly less sensitive to the mitotic spindle poison paclitaxel, effects which could both be modulated via inactivation of p53 and/or Rb. These observations indicate that loss of function of Brca1 in OSE cells impacts both cellular growth control and DNA-damage repair which results in altered cell behavior manifested as morphological changes in vivo that arise earlier and are more numerous than what can be attributed to ageing. It is postulated that loss of Brca1 in the OSE renders these cells susceptible to further genetic aberrations such as loss of other tumour suppressors or activation of oncogenes that could lead to transformation and tumourigenesis.
Keywords: Biology, Molecular.